Regional Economic Integration and Income Inequality in Selected ASEAN Countries - Tan, Ger Ean (Universiti Malaysia Sarawak (UNIMAS), 2020)
Increasing income inequality in recent years has triggered an outpouring analysis and reflection on the causes of these changes. ASEAN has broadened cooperation on macroeconomic and financial aspects and demonstrated robust economic growth, reducing poverty but also accompanied by rising inequality. The income gap persists between ASEAN-5 (Indonesia, Malaysia, the Philippines, Singapore, Thailand) and the ASEAN-3 (Cambodia, Laos, Vietnam) has become a prominent issue and policy debate. Hence, this study aims to investigate the regional economic integration and income inequality by adopting a balanced panel analysis for selected ASEAN countries from 2005 to 2018. To examine the relationship between economic integration and income inequality, economic integration was further decomposed into trade integration and financial integration. Empirical findings showed that trade integration is more effective than financial integration in improving income distribution. Export activities from the manufacturing and service sectors help ASEAN-5, while the agricultural and manufacturing sectors help ASEAN-3 in narrowing income distribution. Therefore, integration policies to improve inequality should not be universally implied on countries with diverse economics structures and varied development activities. Keywords: Regional economic integration, income inequality, ASEAN-5, ASEAN-3.